RETRACTED: Theoretical aspects of knowledge as the key to success and economic growth - Tovma N.A.; Biryuk Larisa; Buryan Maksim; Malgazhdarova Tatyana; Mishenko I.; Tleppayev Arsen (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001